Synthesis of Mesoporous Silica Nanoparticle from Banana Peel Ash for Removal of Phenol and Methyl Orange in Aqueous Solution - Diyana Faziha, Mohamad; Nor Surayah, Osman; Mohd Khairul Hanif, Mohd Nazri; Azizzil Azim, Mazlan; Muhammad Farhan, Hanafi; Yusak Asri, Mohd Esa; Mohd Izzat Ikhwan, Mohd Rafi; Muhammad Naim, Zailani; Nurul Nabihah, Rahman; Abu Hassan, Abd Rahman; Norzahir, Sapawe (Elsevier Ltd., 2019)
In this study, the banana peel ash was used to synthesize mesoporous silica nanoparticles (MSN), and its ability to adsorb methyl orange (MO) and phenol under several different conditions which are effect of pH, effect of adsorbent dosage, effect of initial concentration, and effect of temperature. A batch experiment was conducted to test each of the parameter. The suitable pH for the removal phenol and MO were at pH 5 and pH 3, respectively; with adsorbent dosage was found to be optimum at 0.4 g/L using 10 ppm of phenol and MO, which resulted in 92.6% and 91.1%, espectively at temperature of 343 K. Therefore, the results indicate that the MSN derived from banana peel ash can be used effectively to removed phenol and MO from aqueous media.